Sprinkler system for Stadium UiTM / Nur Lina Abdullah … [et al.] - Abdullah, Nur Lina; Harun, Nurzalina; A. Kadir, Norhidayah; Sadikin, Zubaidah (Research Innovation Business Unit, 2014)
Irrigation system is commonly used in watering lawn and field. There are three basic types of irrigation system, they are the sprinkler, drip and surface which are applicable to work in particular conditions. Sprinkler system is basically used for field applications, based on the size and shape of the area irrigated includes the flow rate and pressure of water supply. Basically, there are four types of water distribution pattern which are full-circle, halfcircle, three quarter-circles and quarter circle. Most manufactures make sprinklers that can be easily adjusted to supply water to almost any portion of a circle. These patterns were designed to avoid overspray beyond the irrigated area. Currently, UiTM stadium’s field with the size of 110 meter length and 72 meter width is watered using the sprinkler irrigation system. Water is distributed through 35 individual sprinklers with 7x5 arrangements so that it breaks up into small water drops which fall evenly to the field. In the actual system, total overlapping area is 7920m^2. The system has too many overlapping area which leads to the waste of water. This proves that the system is inefficient. Therefore, the purpose of this study is to enhance the existing sprinkler’s arrangement that can minimize the number of sprinklers used. A good strategy in managing the sprinkler arrangement is necessary since the amount of water used can be optimizes. This research only considers the radius of water projection as the sufficient condition that must be satisfied in developing new sprinkler arrangement. In order to design possible sprinkler layout, the sprinkler arrangement with less than 7x5 are fitted to the ratio of the field’s length and width is considered. Hence, total number of sprinkler, distance between two sprinklers at length side and width side, radius of water projection and total overlapping area are calculated. The assumption has being made by increasing the distance between sprinklers. It will help to reduce the irrigation overlapping area. By having one meet point between the area covered by four blades (or petals), this helps to reduce uncovered area. There are four possible arrangements that satisfied the four conditions which are; field’s size, total number of sprinkler; sprinkler’s water projection radius; and total overlapping area. However, the results may change depends on the requirement of the operation system. For example, if needs are to minimize the number of sprinkler, they can choose minimum number of sprinklers layout. Likewise, if they want to reduce the cost of water, they can choose amount of sprinklers layout which carried out about minimum number the total overlapping. Validity of the proposed arrangement can be seen in Maplet worksheet. These interfaces are easily accessible by inserting the total number of sprinkler at the length and width. This helps to validate the validity of the proposed sprinkler arrangement. As an overall, this research gives idea in how to arrange a sprinkler in field or in large lawn size. The goals of this research are achieved. The total number of sprinkler is reduced and it can be conclude that the total overlapping area decrease as the distance between sprinklers at length and width increases. Both of these obliquely will minimize the amount of water used and inherently reduced the maintenance cost. If sprinkler arrangement is properly selected, the cost of system will be reduced. Besides, if the systems are properly set up, all uncertainty like overspray and wasted water can be avoided.